1990
DOI: 10.1111/j.1365-2621.1990.tb06797.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Lactic Acid Bacteria and Their Lactases under Acidic Conditions

Abstract: Effects of sonication, survival, and p-galactosidase activity of four lactic cultures were investigated in pH 1.5-3.5 range. Lactobacillur delbruekii subsp. bulgaricus and Streptococcus thermophilus exhibited the highest P-galactosidase activity in skim milk and broth systems, respectively. The P-galactosidases from L. delbruekii subsp. bulgaricus, S. thennophilus, and L. acidophilus showed optimum activity in the neutral pH range and 55°C. Viable count of all four cultures decreased most rapidly at pH 1.5, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(74 citation statements)
references
References 20 publications
4
70
0
Order By: Relevance
“…The viability of probiotic organisms is also influenced by inhibitory components such as lactic acid during fermentation and cold storage. Some other Conditions such as increased acidity resulting from the fermentation process can reduce the survival and viability of probiotic bacteria (16,(20)(21)(22). As mentioned above, we found that L. delbrueckii and L. plantarum could survive the high acidity and low pH in fermented peach juice.…”
Section: Effect Of Cold Storage On Cell Viabilitymentioning
confidence: 58%
“…The viability of probiotic organisms is also influenced by inhibitory components such as lactic acid during fermentation and cold storage. Some other Conditions such as increased acidity resulting from the fermentation process can reduce the survival and viability of probiotic bacteria (16,(20)(21)(22). As mentioned above, we found that L. delbrueckii and L. plantarum could survive the high acidity and low pH in fermented peach juice.…”
Section: Effect Of Cold Storage On Cell Viabilitymentioning
confidence: 58%
“…Although L. acidophilus and bifidobacteria tolerate acid, a rapid decline in their numbers in yogurt has been observed (Shah and Jelen, 1990). …”
Section: Introductionmentioning
confidence: 99%
“…Shah and Jelen [28] reported that Lactobacillus bulgaricus exhibited higher β-galactosidase activity than Streptococcus thermophilus and Lactobacillus acidophillus. Additionally, Wang et al [31] sonicated samples of Lactobacillus delbrueckii ssp.…”
Section: Protease Activitymentioning
confidence: 99%
“…Clark and Martin [27] reported that in the presence or absence of bile acid (Oxgall), B. longumand Lactobacillus bulgaricustolerated bile concentrations as high as 4.0%. Furthermore, Shah and Jelen [28] have attributed increased bile tolerance of Lactobacilli strains to their rigid cell wall. There could be other factors responsible for increased bile tolerance of Lactobacillus bulgaricus and Streptococcus thermophilus when subjected to mild sonication conditions.…”
Section: Figure 1 Growth Of Streptococcus Thermophilus St-m5 At 4˚c mentioning
confidence: 99%